Clasroom Classroom Based Assessment Development for Improving Science Teacher’s Competency in Secondary School at Koto Tangah District - Ardi Ardi; Syam Syamsurizal; Arief Muttaqiin (Pelita Eksakta, 2018)
The aims of developing classroom based assessment for science teacher at secondary school in Koto Tangah district are enhancing the science teacher’s competency and strengthening the principle of developing classroom based assessment. Participants are consisted of 35 junior high school science teacher in Koto Tangah district. Training and workshop method were used in this program to accomplish the goals. Before implementing the program, participants were given a prior knowledge about the basic rules of classroom based assessment. In addition, participants were given the instruction sheets to arrange the classroom based assessment and exercising to develop it with instructor’s guidance.